Parâmetros reprodutivos de Leptodactylus podicipinus (Amphibia: Anura: Leptodactylidae) em ambiente antropizado - Rafael Oliveira Bordin (2021)
Anurans have multiple reproductive strategies, which are intimately associated with the testes germinative dynamics and sperm production. Leptodactylus podicipinus presents a high level of reproductive plasticity and wide geographical distribution, being commonly found in anthropized environments. Although the species has the capacity to reproduce throughout the year, the knowledge about their testes structure in urban habitats is scarce. The present study evaluated the morphological characteristics of the species testes and sperm in an urban environment. Were used 11 males sexually mature from the city of Campo Grande, state of Mato Grosso do Sul, Brazil. The sampling were trough night excursions during the months of April and September, the period occurred in the post rainy season. The biometric data of testes mass, snout-vent length and absolute body mass were associated with sperm parameters variables (length of spermatozoids head and tail). Were performed sperm morphology evaluation and testes stereological calculations. The results presented correlations between testes mass and spermatozoids length, being positive related to the head length and negative related to the tail length. The locular area and the tail length also presented a negative correlation. There were heads and tails of sperm with a morphology different from the pattern described for the species. The germinative structure presented more than 50% of the locular area composed of spermatozoids, 17% spermatids, 16% spermatocytes and 1% spermatogonia. The data contributes to the knowledge of the aspects related to the reproductive biology of Leptodactylus podicipinus from urban environment.